PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT WASILE KABUPATEN HALMAHERA TIMUR - Nurkocim Nurkocim; Nurlaila Nurlaila (Jurnal Manajemen Sinergi, 2016)
The purpose of this studay was to determine and analyse how much influence and discipline of  work to employee performance at at the distrect office wasile Halmahera district east of collection was  done by distributing questionnaires, the analysis method used is multiple resgression analysis wit a  sample of 33 responden. Statistic of test results showed that the t test(partial) control positive and significant effect on the performance (Y) employees at the district. (X1 ) employees and the district, t test (partial) discpine at the district office wasile eastrern Halmahera district, and thus of the test results F (simultaneously) showed that a significant difference between the independent variables namely the supervision and discipline of work on performance (Y) employees at the district office wasile Halmahera Timur district can be recelved.